2014
DOI: 10.1177/2150135114558072
|View full text |Cite
|
Sign up to set email alerts
|

Late Outcomes of Infants Supported by Extracorporeal Membrane Oxygenation Following the Norwood Operation

Abstract: ECMO support following Norwood is associated with high probability of hospital death. Nonetheless, interstage mortality, progression to subsequent palliative stages, intermediate survival, and freedom from heart transplantation are comparable to those in patients who did not require postoperative ECMO support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
(96 reference statements)
1
6
0
Order By: Relevance
“…The report from the SVR trial showed that transplantation-free survival at 2 years was 26% after nonrescue ECMO and 30% after rescue ECMO [9]. Although our hospital survival in ECMO recipients was similar to the results of those studies, we have shown that interstage mortality, progression to subsequent palliative stages, intermediate survival and freedom, from heart transplantation were comparable with those in patients who did not require ECMO support after the Norwood operation [28]. We attribute the favorable outcomes in ECMO survivors to our aggressive policy in identifying and correcting residual lesions and to vigilant follow-up and monitoring after hospital discharge.…”
Section: Commentsupporting
confidence: 82%
“…The report from the SVR trial showed that transplantation-free survival at 2 years was 26% after nonrescue ECMO and 30% after rescue ECMO [9]. Although our hospital survival in ECMO recipients was similar to the results of those studies, we have shown that interstage mortality, progression to subsequent palliative stages, intermediate survival and freedom, from heart transplantation were comparable with those in patients who did not require ECMO support after the Norwood operation [28]. We attribute the favorable outcomes in ECMO survivors to our aggressive policy in identifying and correcting residual lesions and to vigilant follow-up and monitoring after hospital discharge.…”
Section: Commentsupporting
confidence: 82%
“…Similarly, postoperative extracorporeal membrane oxygenation use after the stage I operation is a well-documented factor for early and interstage mortality, and the postdischarge attrition risk is generally attributed to residual lesions, continuous dysfunction, and end-organ injury. 6,7 Although correction of residual lesions is an important principle to improve outcomes in these patients, the remaining issues related to myocardial and end-organ dysfunction are hardly amendable. Finally, the issue of tricuspid valve regurgitation is complex and difficult to address.…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 99%
“…Evidence suggests that single-ventricle infants who require ECLS have worse neurodevelopmental outcomes at 14 months of age than those who do not require ECLS (18). Greater than 80% of Norwood-ECLS hospital survivors are alive five years after hospital discharge (19), underscoring the importance of longitudinal analysis of the impact of neurodevelopmental delay, long-term functional outcome, and costs in these patients.…”
mentioning
confidence: 92%